Exposure therapy : Rethinking the model - refining the method - Wittchen, Hans-Ulrich; Neudeck, Peter (Springer New York, 2012)
Exposure Therapy Rethinking the Model - Refining the Method Peter Neudeck and Hans-Ulrich Wittchen From its early uses in treating phobias, exposure methods have expanded greatly, being established now as state of the art and first-line interventions for all anxiety and many other mental disorders such as post-traumatic stress, obsessive-compulsive, somatoform and addictive disorders. Informed by current understanding of learning, memory, cognition, neurobiology, the neurosciences as well as a range of clinical studies, exposure therapy is now firmly grounded on a broad and robust empirical base, opening new avenues for research and practice in behavioral psychotherapy.  Exposure Therapy: Rethinking the Model -Refining the Method assembles leading experts to create a volume of equal interest and usefulness to students, clinicians and researchers alike. The book critically reviews the theoretical and formal aspects of exposure therapy including ethics; presents the theoretical models and many forms of clinical applications of exposure methods including the relationship to cognitive therapy and acceptance-based approaches; and discusses the role of procedural variants such as imaginal exposure, anxiety control strategies, cognitive interventions, as well as management of safety behaviors during exposure. Core topics are included: Neural substrates of fear extinction and learning. Exposure therapy for anxiety disorders in children. The role of anxiety control strategies in imaginal exposure. Interoceptive exposure and its variants Variants of exposure in body dysmorphic disorder and hypochondriasis. Trauma exposure in PTSD: safety first? Exposure therapy in OCD: are cognitive elements needed? Graduate students, clinicians and scientists seeking an overview on the latest research will look to Exposure Therapy: Rethinking the Model - Refining the Method as a trustworthy guide to the field as it continues to evolve.